Increase of reactive oxygen species in different tissues during lipopolysaccharide-induced fever and antipyresis: an electron paramagnetic resonance study. (4th March 2018) - Gomes, Bruna R. B.; Firmino, Marina; Jorge, Jardeson S.; Ferreira, Maria L. O.; Rodovalho, Thays M.; Weis, Simone N.; Souza, Gloria E. P.; Morais, Paulo C.; Sousa, Marcelo V.; Souza, Paulo E. N.; Veiga-Souza, Fabiane H.
Abstract: Fever is a regulated increase in body temperature and a component of the acute-phase response, triggered mainly after the invasion of pathogens in the body. Reactive oxygen species (ROS) are generated during the physiological and pathological processes, and can act as both signalling molecules as well as promoters of oxidative stress. Male Wistar rats, pretreated with oral doses of acetaminophen, celecoxib, dipyrone, or ibuprofen 30 min before an intravenous lipopolysaccharide (LPS) or sterile saline injection, showed a reduced febrile response in all animals tested. The formation of ROS in the fresh blood, liver, brown adipose tissue (BAT), and hypothalamus of febrile and antipyretic-treated animals was assessed by electron paramagnetic resonance using the spin probe 1-hydroxy-3-methoxycarbonyl-2, 2, 5, 5-tetramethylpyrrolidine (CMH). While the CM concentrations remained unaltered in the blood samples examined 5 h after the induction of fever, we found increased CM levels in the liver (in µM, saline: 290 ± 42; LPS: 512 ± 34), BAT (in µM, saline: 509 ± 79, LPS: 855 ± 79), and hypothalamus (in µM, saline: 292 ± 35; LPS: 467 ± 8) at the same time point. Importantly, none of the antipyretics were seen to alter the CM accumulation profile. Data from this study suggest that there is an increased formation of ROS in the different tissues during fever, which may cause oxidative stress, and that the antipyretics tested do not interfere with ROS production.